Long-term dynamics for stocks of sablefish Anoplopoma fimbria in the western Bering Sea and prospects for their fishery - A. O. Zolotov (Известия ТИНРО)
Sablefish is an endemic species of the North Pacific. Its range extends from California Peninsula, along the Pacific coast of the US and Canada to Aleutian Islands and further, along the Pacific coast of Kamchatka and the Kuriles to the central part of Honshu Island. They dwell also in the Bering Sea and southeastern Okhotsk Sea. Sablefish are the most abundant in the southeastern Bering Sea and in the Gulf of Alaska, that is conditioned by favorable conditions for their larvae and juveniles. In the Asian part of the range, the environments are generally more severe, and reproduction of sablefish is rather risky. Following to the results of modern genetic studies, the sablefish stocks are distinguished by high genetic homogeneity that suggests a common population with the main spawning grounds in the southeastern Bering Sea, at the Pacific coasts of Aleutian Islands, in the Gulf of Alaska, and at the coasts of British Columbia, Washington, Oregon and California. Dynamics of the sablefish biomass is considered on the data of bottom and midwater trawl surveys conducted by TINRO in 2003–2020, fishery statistics, and accessible data of NOAA (USA). Sharp increasing of the biomass and annual catches is noted both in the eastern and western Bering Sea in the last few years because of appearance of several strong year-classes. Western Bering Sea stock depends on migration of recruits from the common spawning grounds in the southeastern Bering Sea. For the western Bering Sea, two main ways of such migration are possible: i) active migration of juveniles with benthic habitat; and ii) passive transfer of pelagic larvae and early juveniles across the Bering Sea through the system of surface currents. The latter mechanism supports the sablefish recruitment in the bays of the western Bering Sea and, to a lesser extent, at the eastern coast of Kamchatka. Sablefish in the West Bering Sea fishery zone were caught in 2010–2020 mostly as by-catch for trawling and longline fishery (93 %), other 7 % were landed by specialized longline fishery. The basic points for managing the sablefish fishery in the West Bering Sea zone are defined. About 400 t of sablefish is permissible to catch annually in the West Bering Sea fishery zone in conditions of modern high stock of this species. This value includes 100–120 t that will inevitably be caught as by-catch and the rest of 280–300 t is a foreseeable resource for organization of specialized fishery.